(untitled) (Indonesian Health Justice Review, 2024)
The COVID-19 pandemic posed significant challenges to Indonesia’s public health system, highlighting critical issues of health justice, human rights, and healthcare equity. This paper analyzes Indonesia’s response to the COVID-19 crisis, focusing on the impact of government measures on marginalized communities and vulnerable populations. Through a review of policy documents, health data, and interviews with public health experts, the study evaluates the effectiveness of Indonesia’s pandemic response in promoting health justice. Key findings reveal that while the government implemented essential health interventions, such as mass vaccination campaigns, the pandemic disproportionately affected the poor, elderly, and residents of rural and remote areas due to unequal access to healthcare resources and information. Additionally, the research examines human rights concerns related to lockdown measures, quarantine policies, and the distribution of medical supplies. The paper concludes by discussing the lessons learned from the COVID-19 crisis and offering recommendations for future health emergencies, emphasizing the need for a rights-based approach to public health that ensures equity, inclusion, and accountability.